Ask for more : 10 questions to negotiate anything - Carter, Alexandra (Simon & Schuster, 2020)
"From the Director of the Mediation Clinic at Columbia Law School, Ask for More shows that by asking better questions, you get better answers-and better results from any negotiation"--